The Impact of Regional Absorptive Capacity on Spatial Knowledge Spillovers - Andrea Caragliu; Peter Nijkamp (Tinbergen Institute, 2008)
We design a conceptual framework for linking two approaches: the literature on absorptive capacity and the literature on spatial knowledge spillovers. Regions produce new knowledge, but only part of it is efficiently adopted in the economy; the share of efficiently adopted technology depends on territorial capital. Our data set is based on a panel of European regions over the period 1999-2005, combining data from EUROSTAT and the European Values Study (EVS); we test the hypothesis that insufficient levels of territorial capital hamper the capability of regions to grasp and fully exploit new knowledge. Results show that a lower regional absorptive capacity increases knowledge spillovers towards surrounding areas, hampering the regions' capability to understand, decode and efficiently exploit new knowledge, both locally produced and originating from outside.
Keywords: O33; R11; 330; Absorptive capacity; knowledge spillovers; total factor productivity; spatial econometrics; Technischer Fortschritt; Regionales Wachstum; Wissenstransfer; Produktivität; EU-Staaten